2004
DOI: 10.1038/sj.ejhg.5201317
|View full text |Cite
|
Sign up to set email alerts
|

PARK11 is not linked with Parkinson's disease in European families

Abstract: Parkinson's disease (PD) is a genetically heterogeneous disease. Recently, significant linkage has been reported to a 39.5 cM region on the long arm of chromosome 2 (2q36-37; PARK11) in North American Parkinson families under an autosomal dominant model of inheritance. We have performed a replication study to confirm linkage to this region in a European population. Linkage analysis in 153 individuals from 45 European families with a strong family history of PD did not show any significant LOD score in this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…A genome-wide association study also confirmed the locus [252], but it was not confirmed in a European linkage study [253]. In 2008, 7 different heterozygous mutations were identified in the GIGYF2 gene (located at the linkage peak) in French and Italian PD cases with family history of PD [172].…”
Section: Park11mentioning
confidence: 97%
“…A genome-wide association study also confirmed the locus [252], but it was not confirmed in a European linkage study [253]. In 2008, 7 different heterozygous mutations were identified in the GIGYF2 gene (located at the linkage peak) in French and Italian PD cases with family history of PD [172].…”
Section: Park11mentioning
confidence: 97%
“…14 Although GIGYF2/PARK11 mutations are actually excluded from the frequent causes of PD in the general human population, [57][58][59][60] GIGYF2 may still play important roles in maintaining neuronal homeostasis and preventing neurodegeneration. Gigyf2 ¡/¡ mice are reported to exhibit perinatal mortality and Gigyf2 C/¡ mice display early onset of age-associated neurodegenerative phenotypes that include neuronal protein inclusion and a significant decline in mobility.…”
Section: Discussionmentioning
confidence: 99%
“…The gene on chromosome 2q36-q37 remains to be identified. Indeed, these results were not replicated recently in a European population [52].…”
Section: Park11mentioning
confidence: 58%